The medicine woman of Galveston - Skenandore, Amanda (Kensington Publishing Corp., 2024)
Once a trailblazer in the field of medicine, Dr. Tucia Hatherley hasn't touched a scalpel or stethoscope since she made a fatal mistake in the operating theater. Instead, she works in a corset factory, striving to earn enough to support her disabled son. When even that livelihood is threatened, Tucia is left with one option--to join a wily, charismatic showman named Huey and become part of his traveling medicine show. Her medical license lends the show a pretense of credibility, but the cures and tonics Tucia is forced to peddle are little more than purgatives and bathwater. Loathing the duplicity, even as she finds uneasy kinship with the other misfit performers, Tucia vows to leave as soon as her debts are paid and start a new life with her son--if Huey will ever let her go. When the show reaches Galveston, Texas, Tucia tries to break free from Huey, only to be pulled even deeper into his schemes. But there is a far greater reckoning ahead, as a September storm becomes a devastating hurricane that will decimate the Gulf Coast--and challenge Tucia to recover her belief in medicine, in the goodness of others--and in herself. --